Globalisation, development, and child rights - Satyarthi, Kailash; Zutshi, Bupinder (Delhi : Shipra, 2006)
Contributed articles presented earlier at a workshop
Includes bibliographical references (p. [283]-294) and index
Keywords: Child labor -- India -- Congresses; Children's rights -- India -- Congresses